A CASE STUDY ON PRE-TENSIONING & POST TENSIONING SYSTEMS OF A PRESTRESSED CONCRETE - Srilaxmi, Veerat; Manju, K.; Vijaya, M. (International Journal of Engineering Technologies and Management Research, 2018)
In Present days the pretensioning and post tensioning systems are very popularly using in the major constructions of a structure. The Pre-tensioning and Post-tensioning both methods are used under pre-stressing process. In which has few edges over the orthodox non-stressed structures like greater span to depth ratio, higher moment and shear capacity. These methods are generally adopted in the making of PSC girders, sleepers, Bridges, Slabs in buildings, Concrete Pile, Repair and Rehabilitations, Nuclear Power Plant etc.